Effectiveness and safety of weekly paclitaxel and cetuximab as a salvage chemotherapy following immune checkpoint inhibitors for recurrent or metastatic head and neck squamous cell carcinoma: A multicenter clinical study - Wakasaki, Takahiro; Manako, Tomomi; Yasumatsu, Ryuji; Hara, Hirotaka; Toh, Satoshi; Masuda, Muneyuki; Yamauchi, Moriyasu; Kuratomi, Yuichiro; Nishimura, Emi; Takeuchi, Toranoshin; Matsuo, Mioko; Jiromaru, Rina; et al. (PLOS ONE, 2022)
Objectives The benefit of sequential therapy after immune checkpoint inhibitor (ICI) treatment for recurrent or metastatic head and neck squamous cell carcinoma (R/M HNSCC) has been recently reported. Furthermore, there is a growing interest in the impact of cetuximab (Cmab)-containing salvage chemotherapy (SCT) and the therapeutic efficacy and adverse events (AEs) of Cmab administration prior to ICI administration. Materials and methods We retrospectively reviewed the medical records of 52 patients with R/M HNSCC treated with SCT (weekly paclitaxel [PTX], n = 7, or weekly PTX and Cmab [PC], n = 45). Results The objective response rate (ORR) and a disease control rate (DCR) was 53.3% and 91.1% in the PC group and 42.9% and 57.1% in the PTX group, respectively. There was a significant difference in the DCR between the PC and PTX groups (p = 0.0143). The overall survival (OS) and progression-free survival were significantly better in the PC group than in the PTX group. On the other hand, the incidence of drug-induced interstitial pneumonia (DI-IP) in R/M HNSCC patients who received SCT was 21.2%. Patients in the PC group were divided according to whether they received Cmab (Group A) or did not receive Cmab (Group B) as palliative therapy prior to ICIs. Group B had a significantly better OS than Group A. Furthermore, our findings suggest that the incidence rate of DI-IP during SCT might be higher in Group B. Conclusion Although PC following ICIs shows dramatic efficacy, careful monitoring of AEs, including DI-IP, is recommended.